RETRACTED: Revisiting Hydrocephalus as a Model to Study Brain Resilience - Oliveira, Matheus F.; Pinto, Fernando C.; Nishikuni, Koshiro; Botelho, Ricardo V.; Lima, Alessandra M.; Rotta, José M. (Frontiers in Human Neuroscience, 2012)
Hydrocephalus is an entity which embraces a variety of diseases whose final result is the enlarged size of cerebral ventricular system, partially or completely. The physiopathology of hydrocephalus lies in the dynamics of circulation of cerebrospinal fluid (CSF). The consequent CSF stasis in hydrocephalus interferes with cerebral and ventricular system development. Children and adults who sustain congenital or acquired brain injury typically experience a diffuse insult that impacts many areas of the brain. Development and recovery after such injuries reflects both restoration and reorganization of cognitive functions. Classic examples were already reported in literature. This suggests the presence of biological mechanisms associated with resilient adaptation of brain networks. We will settle a link between the notable modifications to neurophysiology secondary to hydrocephalus and the ability of neuronal tissue to reassume and reorganize its functions. Key words: hydrocephalus; resilience; brain; neural networks; plasticity.